Do family physicans, emergency physicians and paediatricians give consistent sport-related concussion management advice?. Issue 5 (11th March 2013) - Stoller, Jacqueline; Carson, James; Purcell, Laura; Davidson, Bruce; Garel, Alisha; Bell, Margaret; Snow, Catherine; Law, Marcus
Abstract : Objective: To identify differences and gaps in the recommendations to patients for the management of sport-related concussion among family physicians (FPs), emergency physicians (ERs) and paediatricians (Peds). Design: A self-administered multiple-choice survey, which had been validated for content validity. Setting: Toronto East General Hospital and Markham Stouffville Hospital, both in Ontario, Canada. Subjects: 270 physicians were invited to participate; 104 surveys were completed (39%). Intervention: The survey link was emailed to FPs, ERs and Peds from the above hospitals. Data were analysed using SPSS. Frequencies and percentages were calculated with cross-tabulation of data by specialty. Outcome Measures: Key survey questions identified sources of concussion management information, usefulness of concussion diagnosis strategies, and whether physicians use common terminology when explaining cognitive rest strategies to patients after a sport-related concussion. Results: For making a diagnosis of concussion, 54% of FPs, 86% of ERs and 78% of Peds never used the SCAT2; 49% of FPs, 57% of ERs and 36% of Peds always advised cognitive rest, the mainstay of early management for post-concussion symptoms; 65% of FPs, 71% of ERs and 55% of Peds always advised physical rest; and 49% of FPs, 52% of ERs and 27% of Peds reported no knowledge of any consensus statements on concussion in sport. Conclusions: We identified large gaps in the implementation of recommendations for sport-related concussion patients. Although some physicians are recommending physical and cognitive rest, a large proportion fail to consistently advise this strategy. Better knowledge translation efforts should target all three groups of physicians. Acknowledgements: Thank you to Babak Aliarzadeh for the statistical analysis. Special thanks go to Paul Krueger, Leigh Hayden and the other 18 participants in the validation of our survey. Competing interests: None.